PENGARUH CORPORATE GOVERNANCE TERHADAP VALUE OF THE FIRM DENGAN COST OF CAPITAL SEBAGAI VARIABEL INTERVENING - Gunawan, Anita Jessica (Parsimonia - Jurnal Ekonomi dan Bisnis, 2023)
This study aims to prove the influence of corporate governance variables on the value of the firm. These variables are the size of the board of commissioners, the size of the board of directors, and the independent commissioners. This research was also conducted to determine the direct or indirect influence of the cost of capital variable as a mediation variable in this study. The sample used in this study was a manufacturing company listed on the Indonesia Stock Exchange for the period 2017—2021. The sample obtained in this study was 213 companies. The type of data used in this study is secondary data in the form of company financial statements published by the Indonesia Stock Exchange. The collection technique in this study was carried out with documentation techniques obtained from the published company's financial statements. This research data analysis technique uses Partial Least Squares Structural Equation Modeling (PLS-SEM) with a regression analysis base. The data analysis tool used is SmartPLS 4.0. The results of this study show that the independent commissioner variable has a positive effect on the value of the company, while the variables of the size of the board of commissioners and the size of the board of directors have no effect. The variable cost of capital positively affects the value of the company. On the other hand, the variables of the size of the board of commissioners, the size of the board of directors, and the independent commissioners have no effect on the cost of capital. Similarly, variable capital costs do not affect the mediating effect on the relationship between corporate governance and the value of the firm.